A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species - Loiselle, Paul V. (Zootaxa, 2006)
The history of the genus Pachypanchax Myers, 1933 in the literature is reviewed and the utility of the diagnostic characters proposed by various authors is evaluated. On the basis of five synapomorphies, four skeletal and one squamational, six of the seven presently known Malagasy aplocheilids are found to be unambiguously referable to the genus Pachypanchax. The seventh, Poecilia nuchimaculata Guichenot 1866, known only from the unique type specimen, displays several peculiar skeletal and squamational features. Pending the acquisition of additional material, it is tentatively assigned to the genus. Of the six species treated here, Pachypanchax omalonotus (Duméril, 1861) and P. sakaramyi (Holly, 1828) are redescribed from recently collected topotypical material; and the following four are described as new: P. varatraza., P. patriciae, P. sparksorum, and P. arnoulti. Data on life colors, distribution, natural history and conservation status on all six Malagasy Pachypanchax species are presented.